Joint Attention and Sensitivity to Orienting Gaze in Children with Atypical Development - Smirnova Ya.K. (Психолого-педагогические исследования, 2020)
The article is devoted to the study of the relationship between the mechanism of joint attention and the subsequent normative and atypical development of the child. It is shown that the ability to establish joint attention based on the direction of the interlocutor's gaze is a precursor of the emergence of social and cognitive abilities. The study examined the differences between typical developmental children and atypical development control groups in their ability to be sensitive to social behavioral signals, namely the orientation direction of the interlocutor's gaze. On a sample of 120 children with typical development, mental retardation, hearing impairment, speech disorders and visual impairment, a number of tasks were developed to assess the ability to use the character's direction of sight in the picture to determine its intentions. The task measured such a skill of joint attention as the child’s ability to calculate and report what the other person was looking at and what he intended to choose. We also used tasks with a central hint with an explicit indication of an arrow and a peripheral hint to check the recognition of social and non-social orienting signals. Based on the comparison of contrasting groups, the variability of the formation and age-related changes in skills of joint attention, or rather the presence of differences in recognition, synthesis and interpretation orienting social information coming from eye contact. It was found that children with atpic development have a low level of "downward" joint attention. Impaired joint attention may be one of the earliest signs in children with atypical development at a later age. The results showed that deficiencies in the behavior of joint attention vary depending on mental age and level of development, a sensory defect, so the level of development can really affect the ability of children to joint attention.